Pengembangan Sistem Pencarian OPAC Berbasis Social Shopping - Mardina MH, Riana (Jurnal Pustakawan Indonesia, 2015)
OPAC searching system is developed with the main goal is to facilitate searching information as well as giving the relevant information to the searchers or browsers. Technology web 2.0 facilitate the internet users to interact widely, share idea/information or give comment to one content. The high product selling is influenced by one of the factors, that is, the recommendation from other people or community. Therefore, it can be the opportunity for the librarians to develop OPAC searching system with adopt the technology web 2.0. The users can directly customize and personalize the library services based on the experience of OPAC system. Feedback system with the feature relevance feedback on OPAC means that the users are given space to give input or other information on the searching results, so the document needed is the most relevant document to the users’ needs. Hybrid recommendations feature on OPAC, means the users are given space to get the seraching results based on the similar interest among the other users (content based filtering); and the searching results are also based on  the recomemendation with the greatest or the highest rating (collaborative filtering). The library needs to provide user profile, in order to be the basic of the hybrid recommendations feature development. Searching system with the hybrid recommendation feature and relevance feedback which are adopted from social shopping can be the guidance to develop OPAC searching system based on the technology web 2.0 in the future. Recommendation system which is built can increase the collection use, the source of evaluation to develop collections, information system as well as the library services.Keywords: OPAC, feedback, personalization, relevance feedback, web 2.0, social shopping, hybrid recommendations.